Predicting protein-protein interactions using BiGGER - Almeida, Rui Miguel Lourenço Rocha de (2016)
Fundacao para a Ciencia e Tecnologia (FCT) - PTDC/EIA-CCO/115999/2009; PTDC/BIAPRO/098882/2008; PTDC/BIA-PRO/109796/2009; PTDC/QUI-BIQ/116481/2010 ; FCT-ANR/BBB-BQB/0023/2012; SFRH/BPD/80293/2011; Unidade de Ciencias Biomoleculares Aplicadas-UCIBIO - FCT/MEC (UID/Multi/04378/2013); ERDF (POCI-01-0145-FEDER-007728)